Duplex sonography phlebologically accentuated - Marshall, M. (Phlebologie, 2010)
Without any doubt colour duplex sonography was an enormous progress in angiological and/or phlebological diagnostics. Starting with the directional Doppler sonography, the large spectrum of phlebological diagnostics by colour duplex sonography is presented. Colour duplex sonography is used for a) the fundamental, morphologically and haemodynamically based diagnostics of deep vein thrombosis, of the insufficiency of subfascial and epifascial veins and for differential diagnostic delimitations (of arterial disorders, lip- and lymphedema, Baker-cysts, haematomas and so on), b) intrainterventional controls (steering of endovenous catheters and of foam sclerotherapy), c) the postinterventional assessment of results and disease course (definitively successful elimination of refluxes, relapses, complications as deep vein thrombosis and so on). Finally, the optimal position of the patient for duplex examination – supine or standing – is discussed, and methodical developments of the angiologic-phlebological diagnostics with ultrasound devices are described. Conclusion: In many cases duplexsonography avoids invasive examinations. It is part of the obligatory medical education in the field of phlebology.
Keywords: Doppler sonography; colour duplex sonography; vein disorders; pathophysiology; deep vein thrombosis; insufficiency of the deep veins; insufficiency of the superficial veins